PENYULUHAN PIJAT BAYI BALITA DI PEKON SIDOKATON GISTING TANGGAMUS - Anggriani, Yunita; Komalasari; Agustina, Rika; Isnaini, Maulia; Iis Tri Utami (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Aisyah Pringsewu, 2023)
Baby and toddlers are a vulnerable group in terms of nutritional problems, which must be monitored and provided interventions to produce a quality generation. Fulfilling good nutritional status can affect baby and toddlers' immune system. Giving massage to baby and toddlers can be one of the efforts that can be made to increase endurance and have a positive health impact on toddlers. The aim of this activity is to provide information to mothers who have toddlers regarding the benefits and importance of massage for toddlers, one of the benefits of which is to increase endurance. The material presented in this activity includes the meaning of massage, the benefits of massage and toddler massage techniques. This activity is also carried out directly by carrying out massage demonstrations. The conclusion from holding this activity was that mothers who have toddlers become more knowledgeable and can understand the benefits of toddler massage, and try to apply it little by little in their daily lives. Keywords: Baby Toddler Massage, Body Endurance